International duopoly with unknown costs - F. A. Ferreira (2007)
We consider two firms, located in different countries, selling the same homogeneous good in both countries. In each countrythere is a non negative tariff on imports of the good produced in the other country. We suppose that each firm has twodifferent technologies, and uses one of them according to a certain probability distribution. The use of either one or the othertechnology affects the unitary production cost. We analyse the effect of the production costs uncertainty on the profits of thefirms and also on the welfare of the governments.